Three dimensional kinematic analysis of the long jump at the 2008 IAAF World Indoor Championships in athletics - Campos, J.; Gamez, J.; Encarnacion, A.; Gutierrez-Davila, M.; Rojas, J. (New Studies in Athletics, 2013)
ABSTRACT A description of the technique used by elite jumpers gives insight into individual forms of organisation used to obtain high performance. These models eventually become references that help coaches and athletes to design their own strategies to achieve maximum mechanical efficiency. This paper presents the results of a biomechanical analysis of the men's and women's long jump finals the 2008 IAAF World Indoor Championships in Valencia by researchers from the University of Valencia (Department of Physical Education and Sports), the Institute of Biomechanics at the Polytechnic University of Valencia, and the University of Granada (Department of Physical Education and Sports). The methodology used is based on 3D video photogrammetry. The results show the characteristics of the jumper's individual models in the event. It has been observed that each jumper maintains an individual jumping pattern in relation to timing and in the values obtained in the different kinematic parameters under study. Detailed information on the kinematic parameters is provided.